2020
DOI: 10.3389/fmars.2020.534507
|View full text |Cite
|
Sign up to set email alerts
|

Use of Small Cetaceans as Bait in Small-Scale Fisheries in Peru

Abstract: The use of small cetaceans as bait is a practice that has been reported worldwide, affecting the conservation status of vulnerable species. In Peru specifically, it has been documented since at least the late 1990s. Here we document the various contemporary uses of small cetaceans, including targeted capture for subsequent use as fishing bait. We designed a survey addressing fishery characteristics, bycatch and the use as bait of small cetaceans, and the history of these practice. We surveyed 147 fishers based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Given that the extent of use relative to the size and trends (increasing, decreasing or stable) in the wild source population and rates of immigration and emigration are seldom known accurately, the impact of harvests for aquatic wild meat on the conservation status of source populations can seldom be quantified with any scientific certainty. For example, in mainland South America, it is unclear whether the harvest and trade of small cetaceans specifically for human consumption in Peru was being sustained by the wild population, but from a precautionary stance, increasing rates of harvest for bait or other purposes in Peru, Bolivia, Ecuador, Colombia, Venezuela, and Brazil (Barbosa-Filho et al, 2018;Mintzer et al, 2018;Campbell et al, 2020a;Castro et al, 2020;Briceño et al, 2021) constitute a potential threat. Similarly, the harvest of migratory small cetaceans for aquatic wild meat in the Gulf of Guinea, in particular Atlantic humpback dolphin, which meet IUCN Red List criteria for Critically Endangered (Collins et al, 2017), are assumed to be threatening despite limited information on harvest levels, population size, trends and distribution.…”
Section: Conservation Concernsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that the extent of use relative to the size and trends (increasing, decreasing or stable) in the wild source population and rates of immigration and emigration are seldom known accurately, the impact of harvests for aquatic wild meat on the conservation status of source populations can seldom be quantified with any scientific certainty. For example, in mainland South America, it is unclear whether the harvest and trade of small cetaceans specifically for human consumption in Peru was being sustained by the wild population, but from a precautionary stance, increasing rates of harvest for bait or other purposes in Peru, Bolivia, Ecuador, Colombia, Venezuela, and Brazil (Barbosa-Filho et al, 2018;Mintzer et al, 2018;Campbell et al, 2020a;Castro et al, 2020;Briceño et al, 2021) constitute a potential threat. Similarly, the harvest of migratory small cetaceans for aquatic wild meat in the Gulf of Guinea, in particular Atlantic humpback dolphin, which meet IUCN Red List criteria for Critically Endangered (Collins et al, 2017), are assumed to be threatening despite limited information on harvest levels, population size, trends and distribution.…”
Section: Conservation Concernsmentioning
confidence: 99%
“…The largest exploitation of small cetaceans traditionally occurred in Peru, where they have been caught (intentionally and otherwise) in artisanal gillnets and by harpooning for decades, and sold in local markets or transported to the capital Lima (Read et al, 1988;Van Waerebeek and Reyes, 1994;Van Waerebeek et al, 1999). The use of dolphins as bait has spread to all coastal areas, with annual catches increasing since the early 2000s (Mangel et al, 2010;Tzika et al, 2010;Campbell et al, 2020a). The use of small cetaceans as bait, including dusky (Lagenorhynchus obscurus), common (Delphinus delphis), common bottlenose dolphins, as well as Burmeister's porpoises (Phocoena spinipinnis) (e.g., in longline and gillnet shark fisheries in coastal Peru) appears prolific and has now largely replaced use for human consumption (Van Waerebeek et al, 1999Van Waerebeek and Würsig, 2009;Mangel et al, 2010;Campbell et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Populations of northeastern offshore spotted dolphins (Stenella attenuata attenuata) and eastern spinner dolphins (Stenella longirostris orientalis) have been reduced due to the dolphin bycatch of the purse-seine fishery for yellowfin tuna in the eastern tropical Pacific waters (Gerrodette and Forcada, 2005), although their populations were reported to be increasing in 2006 (Gerrodette et al, 2008). In countries such as Guatemala, Chile, Colombia, Panama, Peru, and Venezuela, dolphin meat has been used as bait for a range of fishing practices (Goodall et al, 1988;Vidal et al, 1994;Culik, 2004;Alfaro-Shigueto et al, 2008;Ávila et al, 2008;Loch et al, 2009;Mangel et al, 2010;Quintana-Rizzo, 2011a;Mel and Fisher, 2016;Mintzer et al, 2018;Campbell et al, 2020). Furthermore, in Guatemala, some fishermen harpoon dolphins because they consider them to be a threat and fishing competitor (Quintana-Rizzo, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…It is confirmed that gillnet bycatch affects the population sustainability of some small cetaceans [6]; especially, the vaquita (Phocoena sinus) is in danger of extinction because of bycatch [7]. Bycatch of small cetacean may have merit to the fishers in many parts of the world (e. g. [8,9]) for consumption or for use as bait in gillnet and longline fisheries [10]. On the other hand, it can also disturb fishing operations [11]: although they are considered 'small' cetaceans, most of the porpoises exceed 1 m in body length; when bycatch occurs, fishers face difficulty removing them from nets.…”
Section: Introductionmentioning
confidence: 99%